Identification of HOXA9 methylation as an epigenetic biomarker predicting prognosis and guiding treatment choice in acute myeloid leukemia - Fei Xie; Ting-juan Zhang; Xin-long Zhang; Zi-jun Xu; Liang Qiao; Yun Wang; Yang-jing Zhao; Jun Qian; Jing-dong Zhou (BMC Cancer)
Abstract Background The homeobox (HOX) genes especially for HOXA cluster play crucial roles in leukemogenesis. HOXA overexpression caused by genetic alterations, such as KMT2A rearrangements, NUP98- fusions and FLT3-ITD mutations, is frequently identified in AML. However, very few studies determined the DNA methylation-mediated epigenetic regulation of the HOXA cluster genes in AML. Methods We systematically first screened the prognostic value of HOXA cluster genes methylation in AML from The Cancer Genome Atlas (TCGA) datasets. Afterwards, the candidate prognosis-related gene HOXA9 were selected for clinical relevance analysis and were further validated in another independent cohort from our research center. Results The methylation of HOXA9, among HOXA cluster genes, negatively correlated with adverse prognosis and expression were screened and identified in AML among TCGA datasets. Clinically, HOXA9 hypomethylation was positively correlated with specific subtypes of AML, such as French-American-British (FAB)-M5/M7, normal karyotype and FLT3, NPM1 and DNMT3A mutation, whereas negatively associated with FAB-M3, t(15;17), t(8;21) and t(16;16). Importantly, AML patients with HOXA9 hypomethylation may profit from transplantation, whereas AML patients with HOXA9 hypermethylation could not, suggesting that HOXA9 methylation may be used to guide therapeutic selection between transplantation and chemotherapy. Bioinformatics analysis demonstrated the association of HOXA9 expression with diverse leukemia-related genes (HOXAs, SOSTDC1, MEG3, miR-10a, miR-381 and miR-193b) and signaling pathways (PI3K-Akt signaling) in AML. Subsequently, we further validate the hypomethylation pattern of HOXA9 in AML patients and the epigenetic regulation of HOXA9 methylation in AML cell-lines. Conclusions HOXA9 methylation linked to HOXA9 expression correlates with diverse genetic abnormalities of AML, such as normal karyotype, t(15;17), t(8;21), t(16;16) and FLT3, NPM1 and DNMT3A mutations. Moreover, HOXA9 hypomethylation may be associated with adverse prognosis, and may guide treatment choice in AML.